Broom-Like and Flower-Like Heterostructures of Silver Molybdate Through Ph Controlled Self Assembly - Singh, D (2012)
Silver molybdate microrods are selfassembled into micron sized, broom-like and flowerlike structures. Our investigations indicate that through a simple hydrothermal process, large scale production of such structure is possible. Using ammonium molybdate and silver nitrate solutions as precursors, we were able to show that the self assembled architectures were dependent on the pH of the starting precursor material. To understand the formation and destructions of the flower-like morphology, a systematic broad range (from acidic to basic) of pH-controlled experiments were performed and its influence on the structure/microstructure of synthesized materials was investigated. Scanning electron microscopy studies revealed that the morphology and microstructure of the products varied significantly by changing pH values from 3 to 8 during mixing of the reactants. pH = 3 and 4 resulted in the self assembly of monoclinic Ag 2(Mo 2O 7) microrods into broom-like structures, whereas pH = 5 resulted into the flower-like morphology of mixed phase of monoclinic and triclinic Ag 2Mo 2O 7. We also found that increasing the pH after a certain threshold value (for example pH>6) resulted in total collapse of the flower-like morphology. Further increase of the pH to 7 and 8 resulted, the formation of microparticles of Ag2MoO 4. A tentative scheme based on the pH-driven evolution of the self-assembly has been given to explain the formation of the observed heterostructures. Preliminary electrical characterization of thin films of the flower-like structures rendered non-linear current-voltage (I-V) responses. We also observed a strong hysteresis in the I-V responses of the flower-like structures developed under high bias conditions. © 2012 Springer Science+Business Media B.V.